Draft genome sequence of the model naphthalene-utilizing organism Pseudomonas putida OUS282 - Tay, Martin (2019)
Pseudomonas putida OUS82 was isolated from petrol- and oil-contaminated soil in 1992, and ever since, it has been used as a model organism to study the microbial assimilation of naphthalene and phenanthrene. Here, we report the 6.7-Mb draft genome sequence of P. putida OUS82 and analyze its featured pathways for biodegradation.